2022
DOI: 10.1159/000521966
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Prechordal Region and an Acroterminal Domain in Amphioxus?

Abstract: This essay re-examines the singular case of the supposedly unique rostrally elongated notochord described classically in amphioxus. We start from our previous observations in hpf 21 larvae [Albuixech-Crespo et al., 2017] indicating that the brain vesicle has rostrally a rather standard hypothalamic molecular configuration. This correlates with the notochord across a possible rostromedian acroterminal hypothalamic domain . The notochord shows some molecular differences that specifically characterize its pre-acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 129 publications
(223 reference statements)
4
7
0
Order By: Relevance
“…It has been suggested that amphioxus does not have a prechordal plate (Neidert et al, 2000). However, recent data highlighted the peculiarity of the anterior axial mesoderm in terms of cell behaviour (Andrews et al, 2021) and of gene expression (Albuixech-Crespo et al, 2017), leading to the proposition of the existence of a 'prechordal process' in amphioxus (Ferran et al, 2022). In line with this suggestion, we propose that amphioxus possesses a structure similar to the vertebrate prechordal plate but only transiently during early embryonic development and that the differences observed in the behaviour of the anterior axial mesodermal tissue between amphioxus and vertebrates are due to the loss of Goosecoid expression during neurulation in the anterior axial mesoderm that expresses Brachyury2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that amphioxus does not have a prechordal plate (Neidert et al, 2000). However, recent data highlighted the peculiarity of the anterior axial mesoderm in terms of cell behaviour (Andrews et al, 2021) and of gene expression (Albuixech-Crespo et al, 2017), leading to the proposition of the existence of a 'prechordal process' in amphioxus (Ferran et al, 2022). In line with this suggestion, we propose that amphioxus possesses a structure similar to the vertebrate prechordal plate but only transiently during early embryonic development and that the differences observed in the behaviour of the anterior axial mesodermal tissue between amphioxus and vertebrates are due to the loss of Goosecoid expression during neurulation in the anterior axial mesoderm that expresses Brachyury2.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the ancestral chordate had a prechordal plate-like structure in the anterior region, or that it had neither anterior notochord nor prechordal plate. If we consider that the ancestral chordate had a prechordal plate-like anterior axial mesoderm, which is the most parsimonious hypothesis if we consider that cephalochordates possess a transient prechordal plate as we and others suggest (Albuixech-Crespo et al, 2017;Andrews et al, 2021;Ferran et al, 2022), we can propose a new evolutionary framework for the appearance of the complex vertebrate head (Fig. 6A).…”
Section: Evolution Of the Vertebrate Head: A Refined Scenariomentioning
confidence: 97%
“…The roof plate of the closed neural tube ends rostrally at the septo-preoptic median bed of the anterior commissure (Figures 1A,A ; fate maps of Puelles et al, 1987;Cobos et al, 2001;Inoue et al, 2000; note His's roofplate was shorter). The prosomeric ventral floorplate stops short of that neural plate ridge, due to its strict co-extensiveness with the underlying notochord, which is its inducer (the floor starts to form by nodal gastrulation of chordal nature caudal to the precocious prechordal plate; see Ferran et al, 2022), whereas the floorplate of His was merely assumed to end at the rostral ridge, similarly, as the basal plate, wrongly holding at the same time that the rostral ridge represents the prospective optic chiasma. The modernly defined anterior end of the floor plate accordingly stops at the mamillary body; see also Puelles et al (2012a), , Puelles (2018).…”
Section: Discussion the Alternative Columnar And Prosomeric Models Of...mentioning
confidence: 99%
“…POG was observed to disappear early in the development accompanying morphogenesis of the pre-chordal plate, and its developmental role has never been clarified [85,91,92]. However, the transient appearance of POG within the pre-chordal plate formation is well documented in many vertebrate embryos [85,88,[92][93][94][95][96][97], further suggesting that POG is a panvertebrate embryonic feature inherited from our ancestor's pharyngeal metameric organization [60].…”
Section: Discussion (A) Serial Homology Of Pog With Vertebrate Pharyn...mentioning
confidence: 99%
“…POG also appears earlier and rostral to the formation of the so-called head cavities, which are epithelial mesodermal coeloms of the vertebrate head [7,8,92,99]. Importantly, the pre-chordal plate was classically described to be intimately connected with the roof of the archenteron at the early rostral embryonic pole [92,9597,100]. This implies that the so-called pre-chordal plate might be of a dual embryonic origin composed of a posterior true axial mesoderm part and an anterior endodermal part, which does not seem to express mesodermal genes and soon disappears [35].…”
Section: Discussionmentioning
confidence: 99%